Prototype Design of a Complete Basic Immunization Information System for Toddlers at the Sedati Community Health Center - Zul Azhri Rustam, Muh; Ayu Riestiyowati, Maya (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
One of the main indicators in measuring the success of immunization activities is the achievement of Universal Child Immunization (UCI). UCI coverage in Sidoarjo Regency for children under two years of age has increased but is still very far from the target set by the local government. Increasing immunization coverage in terms of quantity and quality can take advantage of developments in technology-based information systems. Problems often encountered in the information system contained in one of the posyandu programmed programs, namely the immunization program, are: not yet optimally coordinating data and information between the immunization program and the surveillance system. This research aims to design a complete basic immunization information system for toddlers up to the stage trials. The method used is the information system development method, namely the prototype model. The model consists of several stages, namely: communication, quick planning, quick modeling, construction of prototype, and development delivery & feedback. The results of this research are in the form of a complete basic immunization information system design, which is expected to become material for further applications.